THE ROLE AND IMPORTANCE OF SOCIAL AND POLITICAL INSTITUTIONS IN RAISING THE SENSE OF SPIRITUAL TOLERANCE AMONG YOUNG PEOPLE (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article talks about the role and importance of social and political institutions in raising the moral tolerance of youth.